Dynamics in Systematic Liquidity - Björn Hagströmer; Richard G. Anderson; Jane Binner; Birger Nilsson (Lund University, School of Economics and Management, Department of Economics, 2009)
We develop the principal component analysis (PCA) approach to systematic liquidity measurement by introducing moving and expanding estimation windows. We evaluatethese methods along with traditional estimation techniques (full sample PCA and market average) in terms of ability to explain (1) cross-sectional stock liquidity and (2) cross-sectional stock returns. For several traditional liquidity measures our results suggest an expanding window specification for systematic liquidity estimation. However, for price impact liquidity measures we find support for a moving window specification. The market average proxy of systematic liquidity produces the same degree of commonality, but does not have the same ability to explain stock returns as the PCA-based estimates.
Keywords: G11; G12; 330; systematic liquidity; market liquidity; commonality; dynamic principal component analysis; robust PCA